Portrayal of the West and the Expression of Nepalese Male Ethos in Jungabahadurko Belayet Yatra - Thapa, Dharma Bahadur (Saptagandaki Journal, 2020)
Jungabahadurko Belayet Yatra [Jungabahadur’s England Visit] is a pioneering work of travel account in the Nepalese literature. It recounts Jungabahadur Rana’s formal visit to England and France in 1850 as a goodwill ambassador of the Nepalese king to Queen Victoria while he was the prime minister of Nepal. Although the author is not identified, the work informs the reader of the European life and society with its colour, culture and sound. More than this, it reveals the male ethos of the observer. This paper attempts to analyse the text to see how it represents and reacts to the European society of the mid-fifties of the nineteenth century. The article uses the conceptual frame works of Michel Foucault’s discourse and power and Edward Said’s Orientalism and the generic parameters of travel writing. Finally, the article comes to the conclusion that, despite addressing diverse issues, it portrays England and France mainly in the feminine tropes and presents Rana as the centre of attraction.